Periclimenella agattii sp. nov., a new Palaemonid shrimp (Crustacea, Decapoda, Palaemonidae) from Lakshadweep Islands, India - Bharathi, S.; Purushothaman, P.; Akash, S.; Jose, Sheena; Madhavan, Manu; Dhinakaran, A.; Saravanane, N.; Kumar, T.t. Ajith; Lal, Kuldeep Kumar (Zootaxa, 2019)
The recent collection of Palaemonid shrimps from Agatti Island, Lakshadweep, Arabian Sea, have provided further additions to the Indian marine fauna. In the manuscript, a new species, Periclimenella agattii sp. nov. is described and illustrated. The new species is morphologically most similar to P. spinifera among other congeners, but it strongly differs from that species by having upper the antennular flagellum with 14–16 segments, short free ramus with 12–13 segments, lower antennal flagellum thin and bearing 35–37 segments; 4 minute lateral spines on basal segment of 3rd maxilliped; male palm:carpus ratio of second pereopod higher than in female, propodus of 3rd pereopod with 7–8 ventral spines and hepatic spine with groove. Genetic analysis using the mitochondrial COI and 16S rRNA genes sequences proved that, the new species is significantly distinct from the closed related species.